Integrated structure for a resonant micro-gyroscope and accelerometer - V. Zega; C. Comi; A. Corigliano; C. Valzasina (Fracture and Structural Integrity)
This paper presents the study of the mechanical behavior of a microstructure designed to detect acceleration and angular velocity simultaneously. The new resonant micro-sensor proposed, fabricated by the ThELMA© surface-micromachining technique, bases detection of two components of external acceleration (one in-plane component and one out-of plane component) and two components of angular velocity (roll and yaw) on the variation of frequency of several elements set in resonance. The device, despite its small dimensions, provides a differential decoupled detection of four external quantities thanks to the presence of four slender beams resonating in bending and four torsional resonators.